COUNSELING TO PREVENT AND OVERCOME ANEMIA IN PREGNANT WOMEN WITH A HEALTHY DIET IN WOLUTENGAH VILLAGE, KEREK DISTRICT, TUBAN REGENCY - rahmawati, eva silviana; Safaah, Nurus; Nuraini, Nanik; Erna Eka Wijayanti; eva silviana (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2025)
Anemia during pregnancy is a common condition caused by a deficiency of red blood cells or hemoglobin, leading to reduced oxygen in the body. The main causes of anemia in pregnant women are deficiencies in iron, folic acid, and vitamin B12, which can pose risks to both maternal and fetal health, such as fatigue, premature delivery, and impaired fetal growth. Research shows that a healthy diet rich in iron, folic acid, and vitamin B12 can help prevent and manage anemia. Furthermore, factors such as poor diet, inadequate nutrient intake, and impaired nutrient absorption also contribute to the occurrence of anemia. Regular screenings and iron supplementation are essential for detecting and managing anemia. Health education for pregnant women about the importance of a balanced diet rich in essential nutrients has been shown to increase understanding and awareness about preventing anemia. The education sessions using PowerPoint media demonstrated that pregnant women who participated in this session showed improved knowledge regarding the causes, impacts, and prevention of anemia, as well as the importance of consuming iron, folic acid, and vitamin B12-rich foods. Through effective educational approaches, it is expected that pregnant women will adopt a healthy diet that supports their health and optimal fetal development. Keywords : Anemia during pregnancy, Healthy diet, Iron supplementation